2013
DOI: 10.1016/j.autneu.2013.04.014
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet and age-dependent effects on enteric glial cell populations of mouse small intestine

Abstract: Diabetes and obesity are increasing in prevalence at an alarming rate throughout the world. Autonomic diabetic neuropathy is evident in individuals that experience a long-standing diabetic disease state, and gastrointestinal (GI) dysmotility is thought to be the outcome of neuropathies within the enteric nervous system (ENS) of these patients. To date, an analysis of enteric glial cell population changes during diabetic symptoms has not been performed, and may bring insight into disease pathology and neuropath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 67 publications
(96 reference statements)
0
43
0
Order By: Relevance
“…HF diet-ingesting mice in the current study were previously shown to have high weight gain, epididymal adipose tissue mass, glucose intolerance and insulin resistance compared to mice ingesting a SC diet (Stenkamp-Strahm et al 2013a; Stenkamp-Strahm et al 2013b). Obesity and T2D characteristics were first identified in these mice after 4 weeks of HF diet ingestion, became more progressed at 8 weeks, and markedly progressed after 20 weeks.…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…HF diet-ingesting mice in the current study were previously shown to have high weight gain, epididymal adipose tissue mass, glucose intolerance and insulin resistance compared to mice ingesting a SC diet (Stenkamp-Strahm et al 2013a; Stenkamp-Strahm et al 2013b). Obesity and T2D characteristics were first identified in these mice after 4 weeks of HF diet ingestion, became more progressed at 8 weeks, and markedly progressed after 20 weeks.…”
Section: Methodsmentioning
confidence: 60%
“…Studies by our group have also shown a reduction in total duodenal myenteric neurons, including nNOS/VIP containing neurons, in mice fed a 72% high-fat (HF) diet for 8 weeks (Stenkamp-Strahm et al 2013a). It is well understood that the ENS undergoes a loss of cells in the duodenum and other segments during normal aging (El-Salhy et al 1999; Wade 2002; Stenkamp-Strahm et al 2013b). An analysis of ENS changes in long-standing T2D and parallel age-related changes in animals have yet to be done, however, and will be especially useful to understand GI symptoms in an aging population of human diabetics.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies using type 1 diabetic mice have shown decreases in CNS 47 and colonic levels of GFAP. 48,49 In addition, the expression of GFAP has been reported to decrease in response to acute infection, neurodegeneration, and conditions such as Wernicke's encephalopathy, Down's syndrome, schizophrenia, bipolar disorder, and depression. 50 GFAP-null mice have delayed nerve regeneration following an injury.…”
Section: Discussionmentioning
confidence: 99%
“…12 In contrast, high-fat diet-induced obesity evoked a decline of GFAP and S100b expression in EGCs. 66 Whether these changes depend on diet composition or difference in age remains to be determined. Another disease in which changes in EGCs were recently observed is Parkinson disease.…”
Section: Changes In Egcs In Gastrointestinal Diseasesmentioning
confidence: 99%